PROJETO DE SISTEMA DE LIXEIRAS PARA A ESTAÇÃO RODOVIÁRIA DA CIDADE DE IJUÍ - RAGUZZONI, ALINE N.; SANTANA, JUCIÉLI; COSTA, NATALIA I. D.; ROSA, MONE M. D.; ROSA, TAMARA P. (Salão do Conhecimento, 2013)
Resumo